Wirkungen der Familienpolitik auf die Fertilität in modernen Wohlfahrtsstaaten - Kirschner, Helene (European Journal of Mental Health, 2015)
The Impact of Family Policy on Fertility in Modern Welfare States: Many European welfare states face far-reaching demographic challenges. Concerns about the future institutional stability of modern welfare states are especially heightened by low birth rates. This study examines the impact family policy measures, current regulations in welfare states and socio-cultural transformation have on the fertility rate of a given country. Findings suggest that family policy may have different effects in different contexts, for its impact on fertility depends, ultimately, on the particular social conditions of the given welfare state.